KEPEMILIKAN HAK PAKAI ATAS TANAH BAGI WARGA NEGARA ASING DI KABUPATEN BADUNG PROVINSI BALI - Indra Mandhala Putra, I Putu; Wiratni Darmadi, A.A. Sagung; Sri Indrawati, A.A. (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013, 2013)
Badung Regency in Bali of Indonesia is one of the most favourite tourism spot in Indonesia and even the world. Because of that reason there is many of foreign tourist want to have a land or house in Bali. There are two principles problem in this study: 1) What is type of land rights a foreigners can have in Indonesia? 2) How is the mechanism acquisition of land rights for foreigners in Badung Regency? The result of the research: 1) The type of land rights a foreigners can have in Indonesia is already be regulated in principal land law which is at Act No. 5 Year 1960 (use rights and leasehold rights) 2) The mechanism for acquisition of use rights for foreigners in Badung regency is, first the foreigners must have an agreement with the locals who want to sell or lease their land, after that the locals making right release of their land in public notary in order to change the land rights to the state land which is mean everybody (including the foreigners) can request to the rights of that land.
Keywords: Badung Regency, Land Rights, Foreigners, Land Law